Initiation and regulation of the heartbeat. Issue 5 (May 2015) - Kirkman, Emrys
Abstract The heart has all the components necessary to initiate and maintain a regular heartbeat, without the need for external influence. Thus, a transplanted heart without nervous connection, or a heart completely removed from the body, if adequately perfused with oxygen, beats rhythmically. In the normal intact body, the function of the nervous and humoral regulation is to modulate the activity of the heart, though some aspects of modulation are intrinsic properties of cardiac muscle.